Can an ab initio three-body virial equation describe the mercury gas phase? - Wiebke, Jonas; Wormit, Michael; Hellmann, R.; Pahl, E.; Schwerdtfeger, P. (The journal of physical chemistry. B, Biophysics, biomaterials, liquids, and soft matter, 2014)
We report a sixth-order ab initio virial equation of state (EOS) for mercury. The virial coefficients were determined in the temperature range from 500 to 7750 K using a three-body approximation to the N-body interaction potential.